Enhance The Understanding in Periodic Table of Element Using Crossword Puzzles among Form 4 Students - N. F. A. Rahayu; N. H. Ibrahim; J. Surif (Jurnal Pendidikan IPA Indonesia, 2023)
In this study, the researcher aimed to identify students’ level of understanding of the Periodic Table of Elements before and after using the crossword puzzles called Chem-PTE crossword puzzles. The quantitative approach was used as the methodology of this research and a pre-experimental base was applied to one group as the research design. 25 students were purposely selected as the respondents. The study started with a pre-test, followed by the implementation of Chem-PTE crossword puzzles for 3 lessons and subsequently ended with a post-test. Then, students’ achievement scores in both, pre-test and post-tests, were analysed with descriptive analysis and paired samples t-test by using SPSS software version 24.0. The analyses were conducted to obtain the mean values for both the pre-test and post-test and next to test whether there was a statistically significant difference before (pre-test) and after (post-test) using the Chem-PTE crossword puzzles. Furthermore, this research also examined students’ perspectives on the effectiveness of Chem-PTE crossword puzzles by using questionnaires. Overall, the findings showed that the use of Chem-PTE crossword puzzles had improved students’ level of understanding as there was an increase in students’ achievement scores in the post-test compared with students’ achievement scores in the pre-test. Subsequently, the paired sample t-test analysis also revealed statistically significant differences before (pre-test) and after (post-test) the use of Chem-PTE crossword puzzles. Lastly, almost all of the students provided positive feedback on the effectiveness of the Chem-PTE crossword puzzles in enhancing students’ understanding of the topic Periodic Table of Elements.